2007
DOI: 10.1890/1540-9295(2007)5[261:lesawr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Linking ecosystem services and water resources: landscape-scale hydrology of the Little Karoo

Abstract: There is growing acknowledgement of the dependence of human society on ecosystem services and of the fact that service delivery is being compromised by human impacts on ecosystems. This paper describes the linkage between landscape‐scale hydrology and ecosystem services, and how degradation of the landscape is believed to have altered the delivery of those services. The Little Karoo, an arid environment in South Africa that encompasses a remarkable diversity of plant species, has been degraded by inappropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 11 publications
1
49
0
1
Order By: Relevance
“…Hydrologic ecosystem services (HESs) are beginning to influence land management decisions through both regulations and investments targeted at protecting and improving water resources [Le Maitre et al, 2007;Gordon et al, 2010;Goldman-Benner et al, 2012]. HESs are the goods and services that ecosystems provide to people related to various uses of water, and include water availability for municipal, agricultural, and commercial use, the reduction of the magnitude and frequency of flow peaks to prevent floods, the reduction of sediment and nutrients in water, and the value of natural hydrologic systems for recreation [Brauman et al, 2007; Keeler et al, 2012;Brauman, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrologic ecosystem services (HESs) are beginning to influence land management decisions through both regulations and investments targeted at protecting and improving water resources [Le Maitre et al, 2007;Gordon et al, 2010;Goldman-Benner et al, 2012]. HESs are the goods and services that ecosystems provide to people related to various uses of water, and include water availability for municipal, agricultural, and commercial use, the reduction of the magnitude and frequency of flow peaks to prevent floods, the reduction of sediment and nutrients in water, and the value of natural hydrologic systems for recreation [Brauman et al, 2007; Keeler et al, 2012;Brauman, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…The land-use change from perennial vegetation to crop farming could change the capacity of the soil in retaining and transferring water to the groundwater (Le Maitre et al 2007), and, therefore, making restoration appear as a good option to re-establish some of the lost services. A recent study showed several initiatives of Payment for Ecosystem Services (PES) in Latin America that focus on water provision through the increase of forest cover (Balvanera et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…What is important is not the absolute value, but what proportion it represents of the total available and the total demand, and how sensitive the amount available is to variability in rainfall and the state of the land and ecosystems (Le Maitre et al, 2007a). In the Succulent Karoo the demand exceeds the amount available and the amount is very dependent on rainfall, especially during extended droughts (Le Maitre & O'Farrell, 2008).…”
Section: Value Of the Water Servicementioning
confidence: 99%
“…Water services also play an overarching role in determining many other services related to the agricultural economy of an arid system including soil conservation and nutrient cycling, and in turn, the services of primary production and water provision (Safriel et al, 2005). Therefore promoting catchment integrity to maximise water flows would see the sustainable management of grazing, and in turn the preservation of key ecological elements such as vegetation and soil crusts integrity (Belnap and Lange, 2003), and these in turn are likely to also tie in closely to other regulating and provisioning services (Le Maitre et al, 2007a;Reyers et al, 2009). Increasing population and economic growth will increase demand for this service, however supply, already constrained is most likely to decrease, and innovative approaches to demand side management of this services will become vital in the future.…”
Section: Value Of the Water Servicementioning
confidence: 99%
See 1 more Smart Citation